De novo assembly of a chromosome‐level reference genome of red‐spotted grouper (Epinephelus akaara) using nanopore sequencing and Hi‐C. (14th August 2019) - Ge, Hui; Lin, Kebing; Shen, Mi; Wu, Shuiqing; Wang, Yilei; Zhang, Ziping; Wang, Zhiyong; Zhang, Yong; Huang, Zhen; Zhou, Chen; Lin, Qi; Wu, Jianshao; et al.
Abstract: The red‐spotted grouper Epinephelus akaara ( E. akaara ) is one of the most economically important marine fish in China, Japan and South‐East Asia and is a threatened species. The species is also considered a good model for studies of sex inversion, development, genetic diversity and immunity. Despite its importance, molecular resources for E. akaara remain limited and no reference genome has been published to date. In this study, we constructed a chromosome‐level reference genome of E. akaara by taking advantage of long‐read single‐molecule sequencing and de novo assembly by Oxford Nanopore Technology (ONT) and Hi‐C. A red‐spotted grouper genome of 1.135 Gb was assembled from a total of 106.29 Gb polished Nanopore sequence (GridION, ONT), equivalent to 96‐fold genome coverage. The assembled genome represents 96.8% completeness (BUSCO) with a contig N50 length of 5.25 Mb and a longest contig of 25.75 Mb. The contigs were clustered and ordered onto 24 pseudochromosomes covering approximately 95.55% of the genome assembly with Hi‐C data, with a scaffold N50 length of 46.03 Mb. The genome contained 43.02% repeat sequences and 5, 480 noncoding RNAs. Furthermore, combined with several RNA‐seq data sets, 23, 808 (99.5%) genes were functionally annotated from a total of 23, 923 predicted protein‐coding sequences. The high‐quality chromosome‐level reference genome of E. akaara was assembled for the first time and will be a valuable resource for molecular breeding and functional genomics studies of red‐spotted grouper in the future.